Formación de palabras y su incidencia en la lectoescritura en tercer año de educación general básica. - Ballesteros, Vivien D. (2022)
In the following master's research, the objective should be to implement active methodological strategies to improve the process of word formation and its incidence in literacy, through active methodological strategies. Having as a problem the difficulty in the process of reading and writing, due to ignorance of certain syllables, inverse and compound or double. The methodology that was applied was non-experimental research with a quantitative approach, with a descriptive scope using together the survey technique that allowed us to obtain and collect data quickly and efficiently. Regarding the statistical data, the teachers agreed that improving word formation would automatically improve literacy, taking into account the chisquare results, which allowed us to accept the alternative hypothesis (Ha) since the significance and margin of error was within the range of 5%, therefore it was recommended to improve word formation by applying active methodological strategies to have adequate literacy, improving academic performance. In addition, this research is recommended for future research carried out by teachers with the subject of literacy, methodological strategies and take it as a basis to be able to do a better job and thus evolve the educational level in the institutions where they work. In this research we can realize that with appropriate playful strategies the reading and writing of words, sentences and paragraphs can be improved in a correct way in children with reading and writing difficulties.